Comparative Study on Effectiveness of the aAQUA e-Agriservice among Dairy Farmers of Maharashtra - Wadkar, Sagar Kisan; Singh, Khajan; Kadian, K S; Malhotra, Ravinder; Garde, Yogesh A (Indian Journal of Dairy Science, 2015)
Information is key ingredient for success of any individual, same is true in the case of farmers as well. During last two decades many organizations have undertaken knowledge interventions for promoting scientific farming. Among these interventions that have made significant progress in taking message to the farming community – aAQUA (Almost All Questions Answered) e-Agriservice is one such ICT project has made history and considerable impact in different states of India among the farming community. In present study an attempt was made to evaluate the effectiveness of aAQUA e-Agriservice in terms of knowledge gain about Improved Dairy Farming Practices (IDFPs). Ex-post-facto research design was followed and study was conducted in randomly selected four districts of Maharashtra. The data were collected through personal interview with the help of pre-tested interview schedule comprising demographic characteristics of respondent and developed knowledge test. It was administered on randomly selected 240 respondents (120 each from users and non-users group). About 47.50 per cent of users had high level of knowledge about IDFPs, while one third (33.33%) of non-users had medium level of knowledge. Both the categories of farmers possessed better knowledge about the breeding practices, as compared to the feeding-fodder and health care practices. The users and non-users knowledge had significantly differ at 1 per cent level of significance. At the different levels of education, the knowledge level of users and non-users about IDFPs differed significantly. The study finally revealed that the overall knowledge gain of users of e-Agriservice in IDFPs is quite better than that of non-users due to their efficient utilization of the aAQUA web-portal.